2012
DOI: 10.4161/sgtp.21084
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylation regulates vesicular trafficking of R-Ras to membrane ruffles and effects on ruffling and cell spreading

Abstract: In this study we investigated the dynamics of R-Ras intracellular trafficking and its contributions to the unique roles of R-Ras in membrane ruffling and cell spreading. Wild type and constitutively active R-Ras localized to membranes of both Rab11- and transferrin-positive and -negative vesicles, which trafficked anterograde to the leading edge in migrating cells. H-Ras also co-localized with R-Ras in many of these vesicles in the vicinity of the Golgi, but R-Ras and H-Ras vesicles segregated proximal to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 67 publications
(129 reference statements)
4
39
0
Order By: Relevance
“…Ras proteins undergo prenylation, either farnesylation or geranylgeranylation, for anchoring to inner membranes and FTS functions by inhibiting the prenylation of Ras disrupting membrane localization thereby enhancing their degradation (82, 83). Although FTS blocks farnesylation and inhibits several members of the Ras family including H-Ras, N-Ras and K-Ras, it does not affect R-Ras activity, which unlike other Ras family proteins undergoes geranylgeranylation to anchor to membrane proteins (84). This differential anchoring mechanism provides a target for the development of specific R-Ras inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Ras proteins undergo prenylation, either farnesylation or geranylgeranylation, for anchoring to inner membranes and FTS functions by inhibiting the prenylation of Ras disrupting membrane localization thereby enhancing their degradation (82, 83). Although FTS blocks farnesylation and inhibits several members of the Ras family including H-Ras, N-Ras and K-Ras, it does not affect R-Ras activity, which unlike other Ras family proteins undergoes geranylgeranylation to anchor to membrane proteins (84). This differential anchoring mechanism provides a target for the development of specific R-Ras inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…One intriguing possibility relates to the role of RLIP76 as an effector of the small GTPase R-Ras[19]. We have found that R-Ras recruitment to the plasma membrane is required for its interaction with PI3K (also an R-Ras effector), localized generation of phosphatidylinositol (3,4,5) trisphospate (PIP 3 ), and formation of membrane ruffles and cell spreading[35]. ARNO and other Arf GEFs are recruited to the plasma membrane by interaction with PIP 3 via their pleckstrin homology (PH) domains, leading to localized Arf6 activation which may in turn be the downstream driver of cell spreading and motility[48,49,50,51,52].…”
Section: Discussionmentioning
confidence: 99%
“…NIH 3T3 cells were cultured and transfected, and processed for immunoprecipitations and western blotting as described[35]. …”
Section: Methodsmentioning
confidence: 99%
“…Prolong Gold antifade mounting reagent was from Life Technologies (Carlsbad, CA, USA). GFP-RAS constructs were made as described elsewhere (12,16). GFP-HRAS-(G12V) (Addgene plasmid 18666) was a gift from K. Svoboda.…”
Section: Methodsmentioning
confidence: 99%